The Impact of Systemic Lupus Erythematosus on the Clinical Phenotype of Antiphospholipid Antibody–Positive Patients: Results From the AntiPhospholipid Syndrome Alliance for Clinical Trials and InternatiOnal Clinical Database and Repository. Issue 1 (27th December 2018) - Unlu, Ozan; Erkan, Doruk; Barbhaiya, Medha; Andrade, Danieli; Nascimento, Iana; Rosa, Renata; Banzato, Alessandra; Pengo, Vittorio; Ugarte, Amaia; Gerosa, Maria; Ji, Lanlan; Efthymiou, Maria; et al.
Abstract : Objective: Although systemic lupus erythematosus (SLE) is the most common autoimmune disease associated with antiphospholipid antibodies (aPL), limited data exist regarding the impact of SLE on the clinical phenotype of aPL‐positive patients. The primary objective of this study was to compare the clinical, laboratory, and treatment characteristics of aPL‐positive patients with SLE with those of aPL‐positive patients without SLE. Methods: A secure web‐based data capture system was used to store patient demographic characteristics and aPL‐related clinical and laboratory characteristics. Inclusion criteria included positive aPL according to the updated Sapporo classification criteria. Antiphospholipid antibody–positive patients fulfilling the American College of Rheumatology criteria for the classification of SLE ("aPL with SLE") and those with no other autoimmune diseases ("aPL only") were included in the analysis. Results: Six hundred seventy‐two aPL‐positive patients were recruited from 24 international centers; 426 of these patients did not have other autoimmune disease, and 197 had SLE. The frequency of thrombocytopenia, hemolytic anemia, low complement levels, and IgA anti–β2 ‐glycoprotein I (anti‐β2 GPI) antibodies was higher in the aPL‐positive patients with SLE, whereas the frequency of cognitive dysfunction and IgG anti‐β2 GPI antibodies was higher in the aPL‐only group. The frequency of arterial and venous thromboses (including recurrent) as well as pregnancy morbidity was similar in the 2 groups. The prevalence of cardiovascular disease risk factors at the time of entry into the registry entry did not differ between the 2 groups, with the exception of current smoking, which was more frequent in aPL‐positive patients with SLE. Conclusion: Although the frequencies of thrombosis and pregnancy morbidity are similar in aPL‐positive patients with and those without SLE, the diagnosis of SLE in patients with persistently positive aPL is associated with an increased frequency of thrombocytopenia, hemolytic anemia, low complement levels, and positive IgA anti‐β2 GPI antibodies.